Comparison of the Effectiveness of Sleep Quality with Categories of Using and Not Using Lights while Sleeping in Students - Hilman Mulyana; Deni Wahyudi; Yudi Supriyadi (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
The prevalence of sleep quality in adolescents in Indonesia in women has a high prevalence of 71.3% compared to men, which is 66.4%. One of the factors that affect sleep quality is lamp light, the impact of poor sleep quality can cause mental and physical disturbances for someone Arief 2021. Especially for students who experience decreased concentration and morbidity at school. This study was carried out in June 2022 at Daarul Abroor Vocational School, Tasikmalaya Regency, with the aim of knowing the comparison of sleep quality using and not using light while sleeping in students. This study uses a quantitative method with a cross sectional approach with a population of 162 people. The samples taken in this study were 62 people. The number of samples is categorized by objects that use lights and do not use lights. This study uses the standard Pittsburgh Sleep Quality Index (psqi) instrument. The results of this study found that most of the students who had good sleep quality did not use lamps while sleeping as many as 14 people (45.2%), while students who used lamps when sleeping were 5 people (16.1%). Statistical analysis used in this study using the Chi-Square test and the results obtained significant differences in the quality of sleep using and not using light while sleeping in the students with (p = 0.028).